2007
DOI: 10.1371/journal.pone.0000719
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Placebo-Controlled Trial of a Traditional Chinese Herbal Formula in the Treatment of Primary Dysmenorrhoea

Abstract: BackgroundMost traditional Chinese herbal formulas consist of at least four herbs. Four-Agents-Decoction (Si Wu Tang) is a documented eight hundred year old formula containing four herbs and has been widely used to relieve menstrual discomfort in Taiwan. However, no specific effect had been systematically evaluated. We applied Western methodology to assess its effectiveness and safety for primary dysmenorrhoea and to evaluate the compliance and feasibility for a future trial.Methodology/Principal FindingsA ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
61
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 23 publications
1
61
0
Order By: Relevance
“…Traditional Chinese medicine (TCM), when given for symptom relief, has gained widespread popularity among women with PD [2]. The typical prescriptions of TCM for the treatment of PD are reported as Gegen Decoction, Danggui Shaoyao San, Siwu Tang, Guizhi Fuling Wan, Guizhi Fuling Capsule and so on [6][7][8], which could exert synergistic therapeutic efficacies through multiple regulating humoral immunity and cellular immunity, and releasing inflammatory response [16,17]. In our previous investigation, the bioactive ingredients absorbed into the rat plasma were analyzed, we screened out six ingredients, including gallic acid (from Paeoniae Radix Alba), amygdalin (from Persicae Semen), albiflorin (from Paeoniae Radix Alba), paeoniflorin (from Paeoniae Radix Alba), paeonol (from Moutan Cortex), cinnamic acid (from Cinnamomi Ramulus) which exhibited significant correlation of drug concentration-time curve in rat plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM), when given for symptom relief, has gained widespread popularity among women with PD [2]. The typical prescriptions of TCM for the treatment of PD are reported as Gegen Decoction, Danggui Shaoyao San, Siwu Tang, Guizhi Fuling Wan, Guizhi Fuling Capsule and so on [6][7][8], which could exert synergistic therapeutic efficacies through multiple regulating humoral immunity and cellular immunity, and releasing inflammatory response [16,17]. In our previous investigation, the bioactive ingredients absorbed into the rat plasma were analyzed, we screened out six ingredients, including gallic acid (from Paeoniae Radix Alba), amygdalin (from Persicae Semen), albiflorin (from Paeoniae Radix Alba), paeoniflorin (from Paeoniae Radix Alba), paeonol (from Moutan Cortex), cinnamic acid (from Cinnamomi Ramulus) which exhibited significant correlation of drug concentration-time curve in rat plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these side effects, Chinese medicinal therapy is considered as a feasible alternative medicine for dysmenorrhea. For example, in the previous clinical study, the Chinese herbal formula Four-Agent Decoction (Si Wu Tang) was found to be an effective therapeutic agent for primary dysmenorrhea (48).…”
mentioning
confidence: 99%
“…Si-Wu-Tang [SWT, Si-Wu decoction (Chinese name), Samultang (Korean name), or Shimotsu-to (Japanese name)], comprising the combination of four herbs: Paeoniae ( Radix paeonia alba ), Angelicae ( Radix angelica Sinensis ), Chuanxiong ( Rhizoma chuanxiong ), and Rehmanniae ( Radix rehmanniae preparata ), is one of the most popular traditional medicines for women’s health [1]. It has been used in Eastern Asia for more than one thousand years and ranks first as the most frequently used Chinese medicines [2]. It is an inexpensive over-the-counter preparation used for the relief of menstrual discomfort, climacteric syndrome, peri- or post-menopausal syndromes and other estrogen-related diseases [1,2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been used in Eastern Asia for more than one thousand years and ranks first as the most frequently used Chinese medicines [2]. It is an inexpensive over-the-counter preparation used for the relief of menstrual discomfort, climacteric syndrome, peri- or post-menopausal syndromes and other estrogen-related diseases [1,2,3,4,5]. In previous animal studies, SWT has shown sedative, anti-coagulant, and anti-bacterial activities, as well as a protective effect on radiation-induced bone marrow damage [6,7].…”
Section: Introductionmentioning
confidence: 99%